2020
DOI: 10.1002/etc.4647
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicological Evaluation of UV‐Degraded versus Parent‐Insensitive Munition Compound 1‐Methyl‐3‐Nitroguanidine in Fathead Minnow

Abstract: The US Army is replacing traditional munitions with insensitive munitions resistant to accidental detonation. Although the parent insensitive munition compound nitroguanidine (NQ) is generally not acutely toxic at concentrations >1000 mg/L in aquatic exposures, products formed by intensive ultraviolet (UV) degradation resulted in multiple‐order of magnitude increases in toxicity. A methylated congener of NQ, 1‐methyl‐3‐nitroguanidine (MeNQ), is also being assessed for potential use in insensitive munition expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Among the chemicals suitable for use as constituents in IM formulations, 1-methyl-3nitroguanidine (MeNQ) (Aubert and Roos 2014;Reinke 2016) has had relatively little characterization of potential health and ecotoxicological hazard. While the ecotoxicity of dinitroanisole (DNAN), nitroguanidine (NQ), and nitrotriazolone (NTO), the components of IMX-101, a principal TNT replacement, has been widely investigated (Lent et al 2015(Lent et al , 2016(Lent et al , 2018Lotufo et al 2018;Gust et al 2018Gust et al , 2021Johnson et al 2017;Kennedy et al 2015Kennedy et al , 2017Quinn et al 2014;Stanley et al 2015), only two studies describing MeNQ toxicity in mammalian exposures (Kinkead et al 1993;Reinke 2016) and our laboratory's three recent MeNQ ecotoxicological evaluations (Lotufo et al 2020(Lotufo et al , 2021Gust et al 2021) are the only studies presently available. In these ecotoxicology studies, the lethal effects of MeNQ in both acute and chronic aquatic exposures were only observed at high exposure concentrations (≥ 2186 mg/ L) for a broad range of target species including both aquatic invertebrates (Daphnia pulex, Chironomus dilutus, Lumbriculus variegatus, Hydra littoralis, Hyalella azteca) and vertebrates (Pimephales promelas, Rana pipiens).…”
Section: Introductionmentioning
confidence: 99%
“…Among the chemicals suitable for use as constituents in IM formulations, 1-methyl-3nitroguanidine (MeNQ) (Aubert and Roos 2014;Reinke 2016) has had relatively little characterization of potential health and ecotoxicological hazard. While the ecotoxicity of dinitroanisole (DNAN), nitroguanidine (NQ), and nitrotriazolone (NTO), the components of IMX-101, a principal TNT replacement, has been widely investigated (Lent et al 2015(Lent et al , 2016(Lent et al , 2018Lotufo et al 2018;Gust et al 2018Gust et al , 2021Johnson et al 2017;Kennedy et al 2015Kennedy et al , 2017Quinn et al 2014;Stanley et al 2015), only two studies describing MeNQ toxicity in mammalian exposures (Kinkead et al 1993;Reinke 2016) and our laboratory's three recent MeNQ ecotoxicological evaluations (Lotufo et al 2020(Lotufo et al , 2021Gust et al 2021) are the only studies presently available. In these ecotoxicology studies, the lethal effects of MeNQ in both acute and chronic aquatic exposures were only observed at high exposure concentrations (≥ 2186 mg/ L) for a broad range of target species including both aquatic invertebrates (Daphnia pulex, Chironomus dilutus, Lumbriculus variegatus, Hydra littoralis, Hyalella azteca) and vertebrates (Pimephales promelas, Rana pipiens).…”
Section: Introductionmentioning
confidence: 99%
“…Reinke [2] did an extensive toxicology study involving oral exposures to rats ( Rattus norvegicus ), Lotufo et al. [9] studied toxicological effects of MeNQ on fathead minnows ( Pimephales promelas ), and Gust et al. [10] performed dermal exposures on leopard frogs ( Rana pipiens ).…”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive assessment was recently detailed [11] where the number of species was further expanded to include leopard frog tadpoles, larval midges ( Chironomus dilutus ), blackworms ( Lumbriculus variegatus ), hydrozoans ( Hydra littoralis ), amphipods ( Hyalella azteca ), and cladocerans ( Daphnia pulex ) gaining a more comprehensive toxicity assessment. These studies found that MeNQ was not toxic to their target species, was unlikely to bioaccumulate with a log know of −0.83 [9], but noted changes in microbial communities [10]; however, when MeNQ was UV‐treated, its degradation products had higher toxicity than the parent compound [9, 11].…”
Section: Introductionmentioning
confidence: 99%